Oscillations: Zen & Psychoanalytic Versions - Cooper, Paul C. (Journal of religion and health, 2004)
The author provides a personal and experiential account of Zen Buddhism and psychoanalysis. The notion of oscillations serves as an organizing structure. Drawing from the British psychoanalyst Wilfred Bion and the American Zen teacher Robert Aitken, the notion of suffering, meaning here to permit, is considered as the central motivating force and organizing principle for both disciplines. As a critique of traditional psychoanalytic writing an "experiment in dialogue" is offered that draws from a variety of writing styles including prose, poetry, free-association, stream of consciousness, traditional teaching stories and case material to discuss various experiential states such as linearity, circularity, resistance, ambivalence, passion, rage and the potential for a mutually supportive dynamic between Zen and psychoanalysis.